2001
DOI: 10.1111/1464-0597.00076
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Organisational Support as a Mediator of the Relationship of Perceived Situational Factors to Affective Organisational Commitment

Abstract: Cet article examine le roà le que joue la perception du support organisationnel en tant que me diateur de la relation entre les facteurs situationnels et l'engagement affectif; les facteurs situationnels conside re s e taient: la justice proce durale, une distribution e quitable des taà ches, le degre de satisfaction concernant les rapports avec le supe rieur et le plus ou moins favorable climat des relations de travail. L'analyse des donne es, sur un e chantillon de 185 repre sentants de produits p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 39 publications
4
49
0
6
Order By: Relevance
“…"I take the time to listen to co-workers' problems and worries"; α = 88). Three items adapted from Moideenkutty et al (2001) were used to measure employees' affective organizational commitment (e.g. "I feel a strong sense of belonging to my organization"; α = 0.81).…”
Section: Measurements Regarding Research Questionmentioning
confidence: 99%
“…"I take the time to listen to co-workers' problems and worries"; α = 88). Three items adapted from Moideenkutty et al (2001) were used to measure employees' affective organizational commitment (e.g. "I feel a strong sense of belonging to my organization"; α = 0.81).…”
Section: Measurements Regarding Research Questionmentioning
confidence: 99%
“…There is experimental support for the relationship between justice perception and perceived organizational support (Fasolo, 1995;Ogilvie, 1986;Wayne et al, 2002;Moideenkutty et al, 2001).…”
Section: Perceived Organizational Support As a Mediatormentioning
confidence: 99%
“…Moideenkutty et al (2001) Rhoades, Eisenberger, & Armeli (2001) examined the interrelationships between work experiences, perceived organizational support, affective commitment, and employee turnover. They found that perceived organizational support mediated positive associations of organizational rewards, procedural justice, and supervisor support with affective commitment.…”
Section: Perceived Organizational Support As a Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptions of organizational support can increase employees' commitment to and performance in an organization (Allen, 2001;Eisenberger, Armeli, Rexwinkel, Lynch, & Rhoades, 2001;Moideenkutty, Blau, & Kumar, 2001;Orpen, 1994;Settoon, Bennett, & Liden, 1996). Family-supportive policies are one way in which organizations may demonstrate their consideration of employee well-being, thereby increasing perceived organizational support.…”
Section: List Ofmentioning
confidence: 99%